Znaczenie klauzury w życiu duchowym mniszek. Nauczanie św. Cezarego z Arles - Wygralak, Paweł (Vox Patrum, 2016)
The paper presents the teaching of St. Caesarius of Arles on the subject of the cloister in the life of a nun. It was based on The Letter to Nuns and Rule for Virgins. Caesarian indications are redolent with severity. Under no circumstances were nuns allowed to leave the monastery. They were also very limited in their contacts with the guests, especially with men. All of this was to protect them against the danger coming from such meetings, among which above all the bishop of Arles mentions the temptations against the virtue of chastity. At the same time the monastery is presented as a place safe for the development of all virtues. It is here that every nun finds everything that leads her to the unity with Jesus Christ. That is why her heart should be filled with joy and gratitude towards God.